VD_FINDINFO Jug / 2014 / 5 vom 23. Oktober 2013 - VD Tribunal cantonal (2013)
DÉCISION D'IRRECEVABILITÉ, LANGUE DE LA PROCÉDURE, RETRAIT DU COURRIER, DÉLAI DE GARDE | 403 al. 1 let. a CPP (CH), 85 al. 4 CPP (CH), 16 LVCPP